(untitled) (Global Journal of Human-Social Science, 2022)
Child labour can be found at all stages of the production process in the fashion industry It can be found during the production of cotton seeds in Benin harvesting in Uzbekistan yarn spinning in India right through to the different phases of putting garments together in factories across Bangladesh 1 The problem of child labour is rampantly increasing in the fashion industry since a large part of the supply chain requires low-skilled cheap labour